When a polynomial f ( x ) is divided by ( x − 1 ) and ( x + 5 ) , the remainders are − 6 and 6 respectively. Let r ( x ) be the remainder when f ( x ) is divided by x 2 + 4 x − 5 .
Find the value of r ( − 2 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Write r : = ( x − 1 ) ( x + 5 ) , a 1 = − 6 , \ a 2 = 6 , \ r 1 = x − 1 , r 2 = x + 5 ⟹ s 1 = r 1 r = x + 5 , s 2 = r 2 r = x − 1
then ( x + 5 ) k 1 ≡ 1 m o d ( x − 1 ) ⇒ k 1 = 6 1 ( x − 1 ) k 2 ≡ 1 m o d ( x + 5 ) ⇒ k 2 = − 6 1
f ( x ) ≡ s 1 k 1 a 1 + s 2 k 2 a 2 m o d r ≡ ( x + 5 ) 6 1 ⋅ ( − 6 ) + ( x − 1 ) ( − 6 1 ) 6 ≡ − [ ( x + 5 ) + ( x − 1 ) ]
plug in − 2 and get 0
Problem Loading...
Note Loading...
Set Loading...
When a polynomial f ( x ) is divided by ( x − 1 ) and ( x + 5 ) , the remainders are − 6 and 6 respectively, so we get f ( 1 ) = − 6 and f ( − 5 ) = 6
Because r ( x ) is the remainder when f ( x ) is divided by x 2 + 4 x − 5 , degree of r ( x ) less than 2 .
Suppose that: r ( x ) = a x + b , where a , b are real numbers.
We have: f ( x ) = ( x 2 + 4 x − 5 ) g ( x ) + a x + b
Or f ( x ) = ( x − 1 ) ( x + 5 ) g ( x ) + a x + b .
If x = 1 , then a + b = f ( 1 ) = − 6 ( 1 ) .
If x = − 5 , then − 5 a + b = f ( − 5 ) = 6 ( 2 ) .
From ( 1 ) and ( 2 ) , we have: a = − 2 ; b = − 4 , implying r ( x ) = − 2 x − 4 .
So, r ( − 2 ) = − 2 . ( − 2 ) − 4 = 0